Quality of life of a patient with cancer. Pain and depression – severity of symptoms depending on gender - Komendarek-Kowalska, Monika (Medycyna Paliatywna/Palliative Medicine, 2018)
Cancer is one of the most severe conditions that medicine has to deal with. It is often associated with depressed mood, weakness, and apathy. The patient has a feeling of helplessness and feels the need to isolate himself from the world. These symptoms are intensified in palliative patients, where the pain and limitation of the body’s performance significantly worsen the patient’s emotional state. In many patients, a period of regret, anger and sadness begins when the diagnosis is established. The above conditions often intensify the feeling of pain as an inherent negative symptom of a cancer disease. An analysis of the intensity of pain was carried out in the study, paying attention to differences between sexes. The quality of life of a patient with cancer was also assessed, taking into account anxiety, depression and physical activity. For this purpose, the Visual Analog Scale (VAS) for assessment of pain intensity was used, the Visual Analog Pain Relief Scale, modified scales to assess depression and anxiety (HADS-M) and the Karnofsky Performance Status. After analysis of the data obtained, it was found that about half of the patients diagnosed with neoplastic disease presented symptoms of depression and anxiety disorders, including severe states. These complaints prevailed in female patients. Everyday physical activity was rated as quite good. In terms of pain, the largest group consisted of patients who did not report pain or reported mild pain. The severity of pain was higher in women than in men.